2016
DOI: 10.1111/jnc.13665
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally restricted viral challenge elevates extracellular glutamate and enhances synaptic transmission in the hippocampus

Abstract: Peripheral infections increase the propensity and severity of seizures in susceptible populations. We have previously shown that intraperitoneal injection of a viral mimic, polyinosinicpolycytidylic acid (PIC), elicits hypersusceptibility of mice to kainic acid (KA)-induced seizures. This study was undertaken to determine whether this seizure hypersusceptibility entails alterations in glutamate signaling. Female C57BL/6 mice were intraperitoneally injected with PIC, and after 24 h, glutamate homeostasis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 71 publications
(85 reference statements)
2
23
0
Order By: Relevance
“…, SAL) was approximately threefold higher than the level observed in mice anesthetized with isoflurane (Hunsberger et al . ). This is congruent with previous studies in rats that revealed approximately threefold higher levels in the striatum of freely moving versus anesthetized animals while the respective increase for the cortex was approximately 30‐fold (Rutherford et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…, SAL) was approximately threefold higher than the level observed in mice anesthetized with isoflurane (Hunsberger et al . ). This is congruent with previous studies in rats that revealed approximately threefold higher levels in the striatum of freely moving versus anesthetized animals while the respective increase for the cortex was approximately 30‐fold (Rutherford et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, this increase was only approximately threefold, in contrast to approximately 10‐fold increase in anesthetized mice (Hunsberger et al . ). The cause of this divergence is likely to involve complex neuromodulatory mechanism that might be dependent on the tonic levels of extracellular glutamate.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations